2009
DOI: 10.1563/1548-1336-35.4.176
|View full text |Cite
|
Sign up to set email alerts
|

CaPO4 Blasted Implants Inserted Into Iliac Crest Homologue Frozen Grafts

Abstract: In the last decade, some investigations have reported that the resorbable blast media surface (also named CaPO4 blasted implants [CaPO4-Bls]) has achieved excellent results. However, no report regarding CaPO4-Bls inserted into fresh frozen bone (FFB) is available. Thus, we planned a retrospective study on a series of CaPO4-Bls inserted into FFB to evaluate their clinical outcome. In the period between December 2003 and December 2006, 16 patients (10 females and 6 males, median age of 55 years) were operated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Surface blasting is a process by which metal surfaces are treated with different types of materials (e.g., aluminum oxide, titanium dioxide) to provide an irregular surface 7 . Resorbable blast material (RBM) surface is prepared by sandblasting machined titanium with hydroxyapatite particles containing blast media or calcium phosphate ceramic media 8‐10 . The RBM surface has a higher surface roughness (2.14 μm) than machined surfaces (0.78 μm) 7 .…”
mentioning
confidence: 99%
“…Surface blasting is a process by which metal surfaces are treated with different types of materials (e.g., aluminum oxide, titanium dioxide) to provide an irregular surface 7 . Resorbable blast material (RBM) surface is prepared by sandblasting machined titanium with hydroxyapatite particles containing blast media or calcium phosphate ceramic media 8‐10 . The RBM surface has a higher surface roughness (2.14 μm) than machined surfaces (0.78 μm) 7 .…”
mentioning
confidence: 99%
“…Different studies [21, 23] showed that FFB is a reliable graft material for the reconstruction of lost bony ridge volumes with simultaneous implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Nine RBM surface titanium discs (Neobiotech, Co., LTD, Seoul, Korea) measuring 9 mm in diameter and 3 mm in thickness were used to measure surface properties after burnishing with CHX cotton pellets. The RBM surface was prepared by sandblasting machined titanium with particles containing blast media. The whole of the top surface of the titanium discs was burnished with cotton pellets soaked with 0.12% CHX (Hexamedine Solution ® , Bukwang Pharm, Ansan, Korea) by a single operator (YK) for a total of 20 strokes within 20 s for the first group and 40 strokes within 40 s for the second group.…”
Section: Methodsmentioning
confidence: 99%